Neuroticism biases memory self-report in women. (3rd September 2021) - Bratlee-Whitaker, Emily; Hill, Nikki L.; Mogle, Jacqueline; Bhang, Iris
ABSTRACT: Reports of memory problems are associated with cognitive decline risk and other adverse health outcomes, and the personality trait of neuroticism is known to influence these reports. Since women tend to have higher neuroticism as well as a unique risk profile for cognitive decline, we examined the relationship between neuroticism and responses to two memory self-report items (self- and age-anchored comparisons) among women (n = 1, 132; Mage = 52.71; SD = 13.99) in the Midlife in the United States Refresher Study. Multivariate regression demonstrated that women lower in neuroticism may be more likely to make a distinction between self-comparisons vs. age-anchored comparisons of memory.